Heart failure clinic inclusion and exclusion criteria: cross-sectional study of clinic’s and referring provider’s perspectives - Sherry L Grace; Michael McDonald; Taslima Mamataz; Sean A Virani; Heather Edgell (BMJ Open)
Objectives There are substantial variations in entry criteria for heart failure (HF) clinics, leading to variations in whom providers refer for these life-saving services. This study investigated actual versus ideal HF clinic inclusion or exclusion criteria and how that related to referring providers' perspectives of ideal criteria.Design, setting and participants Two cross-sectional surveys were administered via research electronic data capture to clinic providers and referrers (eg, cardiologists, family physicians and nurse practitioners) across Canada.Measures Twenty-seven criteria selected based on the literature and HF guidelines were tested. Respondents were asked to list any additional criteria. The degree of agreement was assessed (eg, Kappa).Results Responses were received from providers at 48 clinics (37.5% response rate). The most common actual inclusion criteria were newly diagnosed HF with reduced or preserved ejection fraction, New York Heart Association class IIIB/IV and recent hospitalisation (each endorsed by >74% of respondents). Exclusion criteria included congenital aetiology, intravenous inotropes, a lack of specialists, some non-cardiac comorbidities and logistical factors (eg, rurality and technology access). There was the greatest discordance between actual and ideal criteria for the following: inpatient at the same institution (κ=0.14), congenital heart disease, pulmonary hypertension or genetic cardiomyopathies (all κ=0.36). One-third (n=16) of clinics had changed criteria, often for non-clinical reasons. Seventy-three referring providers completed the survey. Criteria endorsed more by referrers than clinics included low blood pressure with a high heart rate, recurrent defibrillator shocks and intravenous inotropes—criteria also consistent with guidelines.Conclusions There is considerable agreement on the main clinic entry criteria, but given some discordance, two levels of clinics may be warranted. Publicising evidence-based criteria and applying them systematically at referral sources could support improved HF patient care journeys and outcomes.